COMPARISON OF FIBRINOGEN LEVELS IN SMOKES THAT SUFFER COPD WITH SMOKING THAT DOESN’T SUFFER FROM COPD - Eko Sudrajad, Amira P. Tarigan & Adi Koesoema Aman (International Journal of Research Science and Management, 2020)
Background Chronic Obstructive Pulmonary Disease (COPD) is a systemic disorder of respiratory disease. Significant complications of COPD can cause hypercoagulable conditions, which can cause life-threatening diseases such as ischemic heart disease, deep vein thrombosis and pulmonary embolism. Therefore, Fibrinogen is a biomarker that is useful for predicting the risk of hypercoagulative conditions in COPD patients.. Methods Sampling was conducted during July 2019. Total population was 60 people (30 COPD patients and 30 nonCOPD patients), the entire population was examined Fibrinogen, Spirometry and Brinkman index, then the results were compared in both populations. The study was conducted after obtaining ethical approval and informed consent. Results There was no difference in the Brinkman Index between the COPD and non-COPD groups with p = 0.369 (p> 0.05). There is a difference in FEV between the COPD and non-COPD groups with a value of p = 0,000 (p <0.05), where the COPD group has a lower FEV than the non-COPD group. There is a Fibrinogen difference between the COPD and non-COPD groups with a value of p = 0, 03 (p <0.05). There was a difference in age between the COPD and non-COPD groups with a value of p = 0.001 (p <0.05), where the COPD group had a higher age than the non-COPD group. Conclusions Increased fibrinogen levels, in stable COPD patients, can be used to assess a prognosis and as a treatment for determining treatment in hospital. Keywords: